Evaluation of pathogen from the FilmArray meningitis/encephalitis panel and recommendations on atypical findings - Luiz Gustavo Ferreira Côrtes; Mariana Menezes Maldonado; Paula Celia Mariko Koga; Kelly Aline de Souza Santiago; Gustavo Bruniera Peres Fernandes; Maira Marranghello Maluf; Marinês Dalla Valle Martino (Arquivos de Neuro-Psiquiatria)
Background Infectious meningoencephalitis is a potentially fatal clinical condition that causes inflammation of the central nervous system secondary to the installation of different microorganisms. The FilmArray meningitis/encephalitis panel allows the simultaneous detection of 14 pathogens with results in about one hour.